Always Already Monsters: ‘BioShock‘’’s (2007) «Splicers» as Computational Others - Švelch, Jaroslav (Nordlit, 2019)
The article explores the manufacturing of monsters in video games, using the case of the influential 2007 first-person shooter BioShock, and ‘splicers’—its most numerous, zombie-like enemies. I combine two methodological perspectives on the ‘manufacturing’ of splicers by analyzing [a] the title’s developer commentary and other official paratexts to trace the design of splicers, and [b] the game’s embedded narrative to reconstruct the diegetic backstory of splicers. I argue that video game enemies, including splicers, are ‘computational others’, who may appear human on the level of representation, but whose behavior is machinic, and driven by computational algorithms. To justify the paradoxical relationship between their human-like representation and machinic behavior, BioShock includes an elaborate narrative that explains how the citizens of the underwater city of Rapture were dehumanized and transformed into hostile splicers. The narrative of dehumanization, explored following Haslam’s dehumanization theory (2006), includes [a] transforming splicers into atomized creatures by depriving them of political power and social bonds, [b] creating fungible and interchangeable enemies through splicers’ masks and bodily disintegration, [c] justifying splicers’ blindness to context and their simplistic behavior by portraying them as mentally unstable addicts. The article concludes that all video game enemies are inherently monstrous, and that critique of video game representation should focus on how games fail to make monsters human, rather than how games render humans monstrous or dehumanized.